PERBANDINGAN METODE AHP DAN TOPSIS UNTUK KEPUTUSAN PEMILIHAN CHIPSET PADA SMARTPHONE - Pratama, Eka Kusuma; Hasan, Fuad Nur (Aksara Public, 2019)
Many smartphone manufacturers offer their products with high-specification chipsets but are not matched with appropriate hardware support devices, which makes the specifications not optimal for cutting production costs. Many chipsets from several manufacturers with the same specifications but produce different performance.Taking into account the existing criteria, the authors use the method Hierarcy Analytical Process (AHP) is used for the main criteria and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) is used for the coupling of strategic alternatives. The data processing software used is the expert choice.This research was conducted to determine the best chipset for a smartphone. The alternative choice of chipset in this study is type 800, type 600 and type 400. From the data I get, it can be seen that chipsets with type 400 are more desirable when compared to other types with a percentage of 42.1%.